Quality Parameters Of Wheat Bread Enriched With Pumpkin (Cucurbita Moschata) By-Products - Kampuse Solvita; Ozola Liene; Straumite Evita; Galoburda Ruta (Acta Universitatis Cibiniensis. Series E: Food Technology, 2015)
Pumpkin processing into puree, juice, candied fruit and pumpkin seed oil results in large amount of by-products. Pumpkins are rich in carotenes, vitamins, minerals, pectin and dietary fibre. The aim of the current study was to evaluate effect of pumpkin pomace and pumpkin residue powder on wheat bread quality. The total content of carotenes was analyzed by spectrophotometric method. The initial increase of pumpkin residue addition indicated increase in loaf volume, which started to decrease at higher amounts. Sensory evaluation (appearance; surface, crust; porosity; texture, crumb; taste, and flavour) of wheat bread with pumpkin revealed very high consumer acceptance except sample with 50% pomace addition. Total carotene content and colour b* value in wheat bread increased by adding pumpkin by-products. It is recommended to add 5% and 10% of pumpkin powder and no more than 30% of pumpkin pomace (calculated per 100 kg of flour) to dough for production of wheat bread with pumpkin by-product additions.